Heavy equipment spare parts inventory system using the Tsukamoto method (case study of PT Berkah Industry Lifting Machinery) - M Mahaputra Hidayat; Eko Prasetyo; Fitri Aulia Damayanti (Jurnal Mandiri IT, 2023)
PT. BIMA located on Jl. Perak Bar. No.379, Surabaya City always maintains the quality of spare parts and maintains port facilities with accurate planning with hundreds of personel who are professionally certified in their fields and have several service services including as one of the suppliers of equipment and spare parts, especially for heavy equipment such as Cranes, Excavators (Bego), Wheel Loaders, Wales Stump and other heavy equipment.  In determining warehouse inventory, the Company can see from the exit of goods periodically either weekly or monthly. What often happens in various warehouses owned by PT. BIMA is in determining the stock of goods. There are times when the goods needed by the consulate are exhausted due to insufficient stock, especially in the monthly period. This research use Fuzzy Tsukamoto to problemsolving control systems that are suitable to be applied to systems, ranging from simple systems to complex or complex systems. Based on the tests that have been carried out In 16 tests, 11 spare parts of goods were obtained with the status of Good Stock information, meaning that the goods can be tested properly by the transaction system every month. Based on the test results of the Good Stock Control Unit 68.75%. Overstock Control Status amounted to 6.25%. The Tsukamoto Fuzzy System used in this research can provide stock recommendations to PT BIMA in a well-maintained stock status.